Optimising an outdoor membrane photobioreactor for tertiary sewage treatment. (1st September 2019) - González-Camejo, J.; Jiménez-Benítez, A.; Ruano, M.V.; Robles, A.; Barat, R.; Ferrer, J.
Abstract: The operation of an outdoor membrane photobioreactor plant which treated the effluent of an anaerobic membrane bioreactor was optimised. Biomass retention times of 4.5, 6, and 9 days were tested. At a biomass retention time of 4.5 days, maximum nitrogen recovery rate:light irradiance ratios, photosynthetic efficiencies and carbon biofixations of 51.7 ± 14.3 mg N·mol −1, 4.4 ± 1.6% and 0.50 ± 0.05 kg CO2 ·m 3 influent, respectively, were attained. Minimum membrane fouling rates were achieved when operating at the shortest biomass retention time because of the lower solid concentration and the negligible amount of cyanobacteria and protozoa. Hydraulic retention times of 3.5, 2, and 1.5 days were tested at the optimum biomass retention times of 4.5 days under non-nutrient limited conditions, showing no significant differences in the nutrient recovery rates, photosynthetic efficiencies and membrane fouling rates. However, nitrogen recovery rate:light irradiance ratios and photosynthetic efficiency significantly decreased when hydraulic retention time was further shortened to 1 day, probably due to a rise in the substrate turbidity which reduced the light availability in the culture. Optimal carbon biofixations and theoretical energy recoveries from the biomass were obtained at hydraulic retention time of 3.5 days, which accounted for 0.55 ± 0.05 kg CO2 ·m −3 influent and 0.443 ± 0.103 kWh·m −3 influent, respectively. Graphical abstract: Image 1 Highlights: Optimum operation was obtained at BRT of 4.5 days and HRT of 1.5–3.5 days. Long BRT of 9 d favoured the proliferation of competing microorganisms. HRT did not significantly affect NRR, photosynthetic efficiency and fouling rate. At optimum conditions, 0.443 kWh·m 3 influent could be recovered.